A Widely Linear Affine LMS Adaptive Algorithm with Momentum Acceleration for DS-CDMA MAI Suppression - Zhou, Yuanjian; Yang, Xiaohui (CIS 2017 : proceedings, 13th International Conference on Computational Intelligence and Security : 15-18 December 2017, Hong Kong, 2017)
A widely linear (WL) affine least mean square (LMS) algorithm with momentum (WL AM-LMS) is proposed to improve the performance of the linear minimum mean squared error (MMSE) multiuser receivers in this paper. The new algorithm is derived from the conventional LMS algorithm by adding affine term and momentum factor. The convergence and the stability region of the proposed algorithm in the mean are analyzed and given out respectively. The performance of the new algorithm applying to direct-sequence code division multiple access (DS-CDMA) multiple access interference (MAI) suppression is investigated by simulation in MATLAB. The experimental results show the effectiveness of the algorithm.